SARS-CoV-2 antibody responses in children exhibit higher FcR engagement and avidity than in adults - Carolyn A. Cohen; Ludivine Grzelak; Susan S. Chiu; David SC Hui; Mike YW Kwan; Owen TY Tsang; Wai Hung Chan; Yat Sun Yau; Kelly WK Lee; Masashi Mori; Gaya K. Amarasinghe; Samuel MS Cheng; et al. (Nature Communications)
Abstract As intrinsic differences in humoral immune response to SARS-CoV-2 between children and adults remain unclear, we improved characterisation by defining the kinetics, specificity and function of antibodies to SARS-CoV-2 in children (n = 146, aged 9.4 ± 4.8 years with n = 257 samples) compared to adults (n = 85, aged 39.5 ± 15.2 years with n = 122 samples). We used plasma samples from an infection and vaccination-naive cohort study with RT-PCR confirmed ancestral B.1* SARS-CoV-2 virus infection with asymptomatic or mild disease, collected in Hong Kong between March to December 2020, from acute (0–14 days post infection) to convalescent (15–206 days) timepoints. Children had significantly lower primary antibody responses against SARS-CoV-2 proteins overall, leading to a less isotype switched response. While children had lower OC43 Spike and SARS-CoV-2 S2 IgG and avidity than adults, they exhibited higher avidities for SARS-CoV-2 whole Spike and Nucleocapsid, and higher levels of Spike FcγR-binding antibodies. Adults’ SARS-CoV-2 antibody responses could be derived from high avidity pre-existing cross-reactive common cold coronavirus B cell responses, whilst children appear to generate a de novo SARS-CoV-2- specific Spike and Nucleocapsid IgG with robust Fc receptor (FcR) binding ability and high avidity at a higher proportion than adults, thus their responses are more targeted and functional for SARS-CoV-2.